STUDI PEMANFAATAN WAKTU PERJALANAN DI DALAM ANGKUTAN UMUM DI INDONESIA - Yosritzal, Yosritzal; Adji, Bayu Martanto; Andika, Revi; Novrizal, Feri (FSTPT Indonesia, 2015)
In conventional travel time studies, the time spent travelling was considered as a wasted time because people the objective of travelling is to arrive and conduct intentional activities at the destination. However, the widespread ownership of personal information and communication technology devices in recent decade has been giving opportunity for travellers to carried out a more productive and enjoyable activities on-board. Researchers found that the use of travel time influences the perception and value of travel time of travellers. This paper presents the findings of a study on how travellers spent their time on-board of public transport in Indonesia. The method used in data collection was focus group discussion.